Larvicidal Activity of Entomopathogenic Fungus, Paecilomyces Specie Against Fourth Instar Larvae of the Mosquito Culex quinquefasciatus (Culicidae: Diptera) - Sani I.; Suleiman M.; Yusuf U; Bandiya H.M. (UMYU Journal of Microbiology Research)
Biological control potential of Paecilomyces spp against Culex quinquefasciatus was evaluated. Paecilomyces spp was isolated from soil using soil suspension method with selective isolation media. Bioassay was made to determine its efficacy against 4th instar larvae of Culex quinquefasciatus. Three different concentrations; 1x106, 1x107 and 1x108conidia/ml were made and tested. Results showed that, mortality increased as the period of exposure increased and also increased as the conidia concentration increased. The mortality recorded in lowest dose of